Systematic Review of Curriculum-Based Measurement with Students Who Are Deaf. (22nd July 2020) - Lam, Elizabeth A; McMaster, Kristen L; Rose, Susan
Abstract: This review systematically identified and compared the technical adequacy (reliability and validity evidence) of reading curriculum-based measurement (CBM) tasks administered to students who are deaf and hard of hearing (DHH). This review included all available literature written in English. The nine studies identified used four CBM tasks: signed reading fluency, silent reading fluency, cloze (write in missing words given blank lines within a passage), and maze (circle the target word given multiple choice options within a passage). Data obtained from these measures were generally found to be internally consistent and stable with validity evidence varying across measures. Emerging evidence supports the utility of CBM for students who are DHH. Further empirical evidence is needed to continue to explore technical properties, identify if student scores are sensitive to growth over short periods of time, and examine whether CBM data can be used to inform instructional decision-making to improve student outcomes.